Desempenho de mudas de alface produzidas nos diferentes volumes de células em bandejas e cultivadas em sistema hidropônico - Lima, Tiago José Leme de (2017)
The hydroponic cultivation of lettuce in the NFT (Nutrient Film Technique) system has use seedlings obtained in trays with smaller volumes, requiring two transplants (from the tray to the nursery and then to the definitive). The use of seedlings produced in larger volumes of cells could provide the transplant directly to the definitive profiles, besides possibly ensuring the smallest cycle of lettuce plant growth in this system. Thus, the objective of this work was to verify the performance of lettuce seedlings produced in different volumes of trays cells and their subsequente transplant aiming at precocity at harvest and exemption from the use of nursery phase in hydroponic NFT system. Two subsequent experiments were performed. In the first experiment, seedlings were grown and evaluated in different volumes cells of trays (50, 40, 35, 31, 30, 29, 27, 20 and 10 cm³ céll-1) and, after 40 days, in the second experiment, Were transplanted directly to the definitive profiles of the NFT, with exception of the seedlings produced in volume 10 cm³ cell-1 that first remained 10 days in the nursery before its definitive transplant. In both experiments, it was adopted a completely randomized block design with four replications. In the seedlings, the following characteristics were evaluated: Plant height (PH cm plant-1); Root lenght of seedlings (RLs cm plant-1); Total leaves of seedlings (TLs leaves plant-1); Fresh seedling aerial mass (FSAM g plant-1); Dry mass of the aerial part of the seedlings (DMAPS g plant-1); Fresh seedlings and root pasta (FSRP g plant-1); Dry mass of seedlings root (DMSR g plant-1). After the transplanting of lettuces in the NFT system, were evaluated at 22 days after transplant (DAT) and 29 (DAT) the characteristics: Number of leaves in senescence (NLS plant-1); Total leaves (TL plant-1); Fresh mass of the aerial part (FMAP g plant-1); Fresh root pasta (FRP g plant-1); Aerial shoot dry mass (ASDM g plant-1); Stem length (ST cm) and Productivity (Kg m-2). The best performance of the seedlings was ally with the increase in volume per cell of trays. After transplant, the best performance of lettuces was generated from the use of seedlings produced in larger cell volumes. In the volumes of 20 to 50 cm³ cell-1, there was no need for the nursery for the seedlings and the number of transplants reduced from two to one, contrary to the volume of 10 cm³ cell-1. Seedlings produced in trays with 40 and 50 cm³ cell-1 provided harvest at 22 DAT of cultivtion in the NFT system.